2003
DOI: 10.3748/wjg.v9.i8.1828
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of peak-to-peak pulsatility of portal blood flow can predict right-sided congestive heart failure

Abstract: The measurement of PP change is a simple and non-invasive way to identify patients with right heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Decrease in portal flow is to some extent compensated by an increase in hepatic artery flow – termed the hepatic artery buffer response . Conditions such as right heart failure, caval stenosis, or veno‐occlusive disease, which increase resistance to hepatic outflow, can sig‐nificantly decrease or reverse the portal flow .…”
Section: Portal Hemodynamics and Liver Regenerationmentioning
confidence: 99%
“…Decrease in portal flow is to some extent compensated by an increase in hepatic artery flow – termed the hepatic artery buffer response . Conditions such as right heart failure, caval stenosis, or veno‐occlusive disease, which increase resistance to hepatic outflow, can sig‐nificantly decrease or reverse the portal flow .…”
Section: Portal Hemodynamics and Liver Regenerationmentioning
confidence: 99%
“… 14 , 15 A pulsatile pattern of portal venous flow is interpreted as the transmission of changes in right atrial pressure across the hepatic veins and the sinusoids to the portal vein. 16 , 17 Abnormal portal vein pulsatility (PVP) has been demonstrated to correlate with elevated right atrial pressures 18 and bowel edema in patients with HF, 19 suggesting the potential use of this metric as a noninvasive tool for the assessment of splanchnic compartment. Notably, increased venous congestion along with severe tricuspid regurgitation (TR) related to right heart dysfunction, and altered compliance of the hepatic vascular bed are mechanisms suggested to result in portal hypertension and therefore lead to a markedly pulsatile portal flow.…”
mentioning
confidence: 99%
“…Also, Jui-Ting Hu, et al 2003 who studied the peak-to-peak PI of portal blood flow in order to predict the right-sided congestion in CHF patients. They concluded that the measurement of Portal vein flow changes identify patients with CHF (7) . This finding adds more evidence to our result.…”
Section: Discussionmentioning
confidence: 99%